Burglary victimisation in England and Wales, the United States and the Netherlands: a cross-national comparative test of routine activities and lifestyle theories - Andromachi Tseloni; Karin Wittebrood; Graham Farrell; Ken Pease (2004)
Burglary victimisation in England and Wales, the United States and the Netherlands: a cross-national comparative test of routine activities and lifestyle theories